Cluster thinning in high altitude vineyards and wine quality from the cultivar Syrah Raleio de cachos em vinhedos de altitude e qualidade do vinho da cultivar Syrah - da Silva L.C. (2009)
The objective of this work was to evaluate the effect of different intensities of cluster thinning in mountain vineyards cv.Syrah on the evolution of phenolic compounds, during grape maturation. The experiment was carried out in the 2005/2006 and 2006/2007 crop seasons, at São Joaquim, SC, Brazil, at an average altitude of 1,230 m, on 'Syrah' grapevines that had been grafted on 'Paulsen 1103' root stock and trained out in vertical trellis system, spaced in 3×1.2 m and protected against hail. The cluster thinning was adjusted in the "veraison" corresponded to 15 Mg ha-1 (control), 13 Mg ha-1, 11 Mg ha-1 and 9 Mg ha-1, in a complete randomized blocks. The evolution of phenolic compounds was evaluated during the eight antecedent weeks to the harvest. The cluster thinning increased the content of anthocyanin in the grapes with a yield of 12 Mg ha-1, and improved their phenolic composition. These changes were favorable for the production of fine wines with excellent quality. © 2009 Embrapa Informação Tecnológica.